Plötzlicher Herztod: Epidemiologie, Pathophysiologie und Risikostratifizierung = Sudden cardiac death : epidemiology, pathophysiology and risk stratification - Rudic, Boris; Tueluemen, Erol; Liebe, Volker; Kuschyk, Jürgen; Akın, Ibrahim; Borggrefe, Martin (Herz, 2017)
Sudden cardiac death (SCD) remains a major public health burden despite revolutionary progress in the last three decades in the treatment of ventricular tachyarrhythmia with the use of implantable cardioverter defibrillator (ICD) therapy. Survivors of sudden cardiac arrest are at high risk for recurrent tachyarrhythmia events. Early recognition of low left ventricular ejection fractions (≤35%) as a strong predictor of mortality and the causal association between ventricular tachyarrhythmia and SCD has led to a significant development of not only pharmacological antiarrhythmic therapy but also device-based prevention of SCD. The ICD therapy is nowadays routinely used for primary prevention of SCD in patients with significant structural cardiomyopathy and primary electrical arrhythmia syndromes, which are associated with high a risk and secondary prevention in survivors of sudden cardiac arrest. Additionally, effective approaches exist to significantly reduce the recurrence rate of ventricular tachyarrhythmia of various origins by complex electrophysiological endocardial and epicardial catheter ablation procedures.